Praktična uporabnost reduciranega modela ekspertnega sistema potencialne uspešnosti v prostoru morfološko-motoričnih razsežnosti mladih košarkarjev - Erčulj, Frane (Šport (Ljubljana), 2018)
Based on expert knowledge and years of research, the Faculty of Sport, University of Ljubljana has developed many multi-stage models of expert systems for establishing basketball players' potential performance (their potential). This study presents and validates a heavily reduced model which is composed of three morphological and five motor dimensions that affect substantially playing performance in basketball. The results of the model validation that was based on measurements of 41 young basketball players from two national basketball teams (U15 and U16) as well as assessments of actual and prognostic performance made by six basketball experts (coaches) show a low correlation between the assessments of potential and playing performance, namely the correlation does not achieve the threshold of statistical significance. Correlation between assessments of potential and actual performance (r = 0.22) is slightly higher than that between assessments of potential and prognostic performance (r = 0.09). The low correlation undoubtedly requires a change in relations among variables is considered as well as a change in the definition of weights and normalisers. It is clear that the model will have to be expanded by a number of variables measuring abilities and characteristics that have not been included in the current model.
Keywords: ekspertni sistemi; košarka; košarkarji; morfološke lastnosti; motorične sposobnosti; validacija